PENERAPAN PENGOLAHAN DATA DENGAN PRIVATE CLOUD UNTUK PEMINJAMAN DOKUMEN STUDI KASUS PADA PT TIRTO JAKARTA - Sapta Pranata Harta; Hendra Kusworo (CKI ON SPOT, 2016)
File management application documents used in PT Tirto Jakarta currently quite helpful in completing the task of document management in the system application is pretty good in terms of data security, quality performance and also allows the user to make the process of document management and are expected to make it easy for any user to operate and facilitate the lending transaction documents, Development loan documents on PT. Tirto Jakarta is not effective and efficient lending system because the document has not been terkompouterisasi. Absence standard operating procedure (SOP). which aims to provide facilities for the implementation of activities in terms of lending documents and search for documents that could tell which documents are void or are still in the borrower documents. Therefore, by using the methods System Development Life Cycle (SDLC). can assist in improving the lending system that can be controlled and documents can also be effective and efficient. Keywords: file document, SDLC, PT Tirto Jakarta